Robot's adaptive emotional feedback sustains children's social engagement and promotes their vocabulary learning: a long-term child–robot interaction study. (August 2019) - Ahmad, Muneeb Imtiaz; Mubin, Omar; Shahid, Suleman; Orlando, Joanne
In this article, we present an emotion and memory model for a social robot. The model allowed the robot to create a memory account of a child's emotional events over four individual sessions. The robot then adapted its behaviour based on the developed memory. The model was applied on the NAO robot to teach vocabulary to children while playing the popular game 'Snakes and Ladders'. We conducted an exploratory evaluation of our model with 24 children at a primary school for 2 weeks to verify its impact on children's long-term social engagement and overall vocabulary learning. Our preliminary results showed that the behaviour generated based on our model was able to sustain social engagement. In addition, it also helped children to improve their vocabulary. We also evaluated the impact of the positive, negative and neutral emotional feedback of the NAO robot on children's vocabulary learning. Three groups of children (eight per group) interacted with the robot on four separate occasions over a period of 2 weeks. Our results showed that the condition where the robot displayed positive emotional feedback had a significantly positive effect on the child's vocabulary learning performance as compared to the two other conditions: negative feedback and neutral feedback.